Conformational proteomics of macromolecular architecture : approaching the structure of large molecular assemblies and their mechanisms of action - Cheng, R. Holland; Hammar, Lena (World Scientific Pub., 2004)
Biological processes involving large macromolecular assemblies arethought to be a dynamic consequence of cooperativity andmetastability. The folding of a peptide chain creates localenvironments from which "activity" can emerge. In the same way, theassembly of large molecular complexes creates dynamic features thatwould only be feasible in a large construct. The biologicalimplications of such adaptation will be explored as it applies to thestatic quasisymmetry situations, as well as to the dynamics ofstructural transitions. The current wealth of solved high-resolutioncomplex structures makes th